From Local Identity to Global Reach: Enhancing MSMEs through Education and City Branding - Muhammad Heru Hresnawanza; Ahmad Khoirin Andi (Al-Qalam Institue, 2025)
This study aims to analyze the implementation of BRK (Bondowoso Republic of Coffee) city branding in the management and marketing strategies of DOA Coffee MSMEs, and its impact on strengthening brand identity and the competitiveness of local products. The method used is a case study with a qualitative approach, involving interviews with business actors, coffee farmers, and related communities. The survey results indicate that implementing BRK city branding strengthens DOA Coffee's brand equity by increasing geographic legitimacy and fostering synergy among farmers, roasteries, and the tourism sector. Product differentiation strategies, storytelling, and digital marketing increase brand awareness and customer loyalty. In addition, glocal marketing and distribution through partnerships with tourist destinations and souvenir outlets expand market reach. The implications of this study indicate that BRK city branding can increase the competitiveness of coffee MSMEs by leveraging local identity and integrated marketing strategies. These findings contribute to the development of MSME strategies grounded in local potential and provide insights for business actors and the government in building a creative economy based on regionally superior products, with an emphasis on the role of education in enhancing MSME actors' capabilities.